Adsorption and catalysis of graphene in environmental remediation - Sun, H.; Wang, Shaobin (2016)
© 2016 by Taylor & Francis Group, LLC. This chapter introduces the versatile applications of graphene as adsorbents, supporting and hybridization materials, and catalysts for removal of pollutants in contaminated water and air. The strong adsorption for many types of pollutants, such as gases, heavy metals, inorganic anions, dyes, and many other organic contaminants, on graphene and graphene oxides is discussed. Insightful mechanism of structure-related adsorp tion and the effect of functional groups (epoxys, hydroxyls, and carboxylic groups) on the adsorption will be studied. The large surface area, porosity, surface charges, and functional groups are considered as the key roles for adsorption of dif ferent pollutants. Recent research also showed that graphene or its oxide is able to be used as a catalyst in advanced oxida tion processes (AOPs) by means of photocatalysis or chemical oxidation. The active sites and related charge transfers in the catalysis with or without irradiation are discussed. The find ings open a venue to green catalysis that employs novel and nontoxic metal-free catalysts for AOPs, leading to a sustain able remediation strategy.